Cognitive Resilience Amongst the Elderly in Socah Village's Fishing and Non-Fishing Communities - Adiwinoto, Ronald Pratama; Putri, Ida Ayu Govinda Lazenobia De Sanjaya; Wendra, Sadya; Liliawanti, Liliawanti; Herdiyantini, Mita; Putra, Oki Nugraha; Adnyana, I Made Dwi Mertha (GLOBAL HEALTH SCIENCE GROUP, 2024)
Alzheimer's Indonesia (ALZI) reports a significant and growing prevalence of Orang Dengan Demensia Dementia (ODD), which is projected to reach 2 to 4 million individuals by 2050. Dementia is often attributed to cognitive deficits, prompting this study to investigate and compare the Community Mini Mental State Examination (MMSE) scores among elderly professionals, specifically fishermen and non-fishermen, residing in Socah Village, Bangkalan, East Java. Objective: This research aims to elucidate the extent of cognitive impairment in this demographic. Method: An analytical observational study employed a purposive sampling approach, with a total sample size of 96 individuals. The age categories ranged from 45 to 89 years, adhering to the Badan Pusat Statistik 2015 guidelines. Data collection took place during August to September 2022. Results: The results of the Mann-Whitney's test indicate a significant difference in Mini Mental State Examination (MMSE) scores between elderly fishermen and non-fishermen in Socah Village, with a p-value of 0.001 (p < α, α = 0.05). Conclusion: This finding leads to the conclusion that there is a notable disparity in MMSE scores among elderly professionals, highlighting the substantial impact of physical activity on cognitive function.